Windows NT in a nutshell : - Pearce, Eric (O'reilly, 1997)
Anyone who installs Windows NT, creates a user, or adds a printer is an NT system administrator (whether they realize it or not). This book organizes NT's complex 4.0 GUI interface, dialog boxes, and multitude of DOS-shell commands into an easy-to-use quick reference for anyone who uses or manages an NT system. Windows NT in a Nutshell will be as useful to the single-system home user as it will be to the administrator of a 1,000-node corporate network. This book: Presents the GUI hierarchy with callouts to provide easy-to-locate documentation of options, buttons, and dialogs. Covers DOS-shell commands in great detail, since these come into increasing use by the experienced NT user when managing large and complex installations